A gestão da informação na implementação do Programa Mais Educação na rede estadual de ensino de Sergipe - Santos, Diana Viturino (2015)
This study analyses the information management of Sergipe s State Secretariat of Education in the context of implementing the Programa Mais Educação. The implementation process of given public policies is a dynamic process, during which managers make decisions instead of just putting previously formulated decisions into action. However, making appropriate decisions depends, besides other factors, on information. Therefore, the question arises, how the State Secretariat of Education of Sergipe manages information regarding the implementation of the Programa Mais Educação (PME). The general objective of this research is to analyze the management of information available to the Secretariat, with a view to the implementation of PME. To reach that purpose, more specific objectives were formulated: 1) systematize sources of information; 2) systematize types of information; 3) systematize channels of information; 4) analyze conduct with these information and 5) to analyze use of these information. To study these objectives, a research approach including bibliographic and documental research, as well as a qualitative case study, based on data collected from direct observation and semi-structured interviews with program managers within the state network of education, was chosen. The obtained data was analyzed on the basis of information management models. This research recognized the diversity of tasks, challenges and problems faced during implementation of the Programa Mais Educação, parting form the experiences of those responsible for coordinating the process. The study identified an emphasis on tactical management tasks, which is also reflected in the information management sector. The information is directed to attend immediate necessities, considering the absence of any strategic planning which would permit a more analytic view on the obtained or produced information in the range of the program.